2007
DOI: 10.1136/ard.2007.075424
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association of interleukin-21 polymorphisms with systemic lupus erythematosus

Abstract: Objective: The aetiology of systemic lupus erythematosus (SLE) is incompletely understood. Both genetic and environmental factors are implicated in the pathogenesis of the disease. Herein, we describe genetic association between SLE and polymorphisms in the interleukin (IL)-21 gene. The reported effect of IL-21 on B-cell differentiation into plasma cells and its effect on dendritic cell maturation and T-cell responses make IL-21 an attractive candidate gene for SLE. Methods: Three single nucleotide polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
132
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(141 citation statements)
references
References 19 publications
5
132
2
Order By: Relevance
“…IL-2 is predominately a T cell-derived cytokine that promotes B cell proliferation and enhances the effects of IL-21 in inducing plasmablast by CD40L stimulation (19,28,29). The levels of both cytokines are altered in SLE and thought to play a role in pathogenesis (30)(31)(32)(33).…”
mentioning
confidence: 99%
“…IL-2 is predominately a T cell-derived cytokine that promotes B cell proliferation and enhances the effects of IL-21 in inducing plasmablast by CD40L stimulation (19,28,29). The levels of both cytokines are altered in SLE and thought to play a role in pathogenesis (30)(31)(32)(33).…”
mentioning
confidence: 99%
“…In B cells, the effect of IL-21 is dependent on their stage of differentiation, such that engagement with naïve B cells confers an apoptotic signal while it promotes T cell-dependent maturation of antigen-experienced B cells to plasma cells (12,13) and is essential for germinal center (GC) formation (6). Recent studies in humans suggest that allelic variation in the IL-21 gene is a risk factor for SLE (14). Previous work showed that BXSB-Yaa mice have elevated IL-21 at the transcriptional and serum protein levels (12).…”
mentioning
confidence: 99%
“…50,69 In humans, higher serum IL-21 and IL-21 mRNA levels were observed in SLE patients, 87,88 and population-based case-control association analyses suggest that allelic variation in the IL-21 gene was a risk factor for SLE. 87 In a study evaluating SLE patient autologous mixed CD3 1 T-and CD19 1 B-lymphocyte cultures, the exogenous addition of IL-21 and/or CpG-ODN2006 caused a significant increase in secreted IgG and the PC proportion reduced following IL-21R.Fc treatment.…”
Section: Il-21/il-21r and Slementioning
confidence: 99%
“…50,69 In humans, higher serum IL-21 and IL-21 mRNA levels were observed in SLE patients, 87,88 and population-based case-control association analyses suggest that allelic variation in the IL-21 gene was a risk factor for SLE. 87 In a study evaluating SLE patient autologous mixed CD3 1 T-and CD19 1 B-lymphocyte cultures, the exogenous addition of IL-21 and/or CpG-ODN2006 caused a significant increase in secreted IgG and the PC proportion reduced following IL-21R.Fc treatment. 4 In SLE murine models, the lupus BXSB-Yaa mouse showed increased IL-21 at the transcriptional and serum protein levels compared to wild-type mice 69 and the genetic deletion of IL-21R in these mice led to the disappearance of abnormal SLE characteristics, including hypergammaglobulinemia, autoantibody production and renal disease.…”
Section: Il-21/il-21r and Slementioning
confidence: 99%